Influence Of Water Spraying In The Cooking Process Of Baked Churros On Customer’s Acceptance - Dina Safina Fadhliani; Yati Setiati; Ridawati Ridawati (Universitas Negeri Padang, 2021)
This study aims to examine the influence of water spraying in the cooking process of baked churros on customer’s acceptance , which includes aspects of color, aroma, taste, pores and texture. The study was conducted from January 2020 to March 2020 at the Culinary Analysis and Engineering Laboratory, Faculty of Engineering, Jakarta State University. In this analysis, extra treatment was provided to baked churros in the form of spraying water prior to the baking process. This study used an organoleptic test which was tested on 3 expert panelists (Culinary Education Lecturers) and 30 untrained panelists. The hedonic test results showed that by spraying water with P2, the highest average customer’s acceptance of baked churros seen from the aspects of color, aroma, taste, pores and inner texture was vulnerable to like. The Friedman test with a significant level of α = 0.05 was used in the results of the study. The Friedman test results showed that the treatment did not affect the aspects of color, aroma, taste, inner texture and outer texture, but that it had an effect on the pore aspects. Tuckey's test results showed that in the cooking of baked churros, spraying P2 water was most favored by consumers. Based on these findings, the production of baked churros by spraying water with P2 can be recommended as a result of the best water spraying baked churros.